Tick-borne pathogens in Finland : comparison of Ixodes ricinus and I-persulcatus in sympatric and parapatric areas - Laaksonen, Maija; Klemola, Tero; Feuth, Eeva; Sormunen, Jani J.; Puisto, Anna; Mäkelä, Satu; Penttinen, Ritva; Ruohomäki, Kai; Hänninen, Jari; Sääksjärvi, Ilari E.; Vuorinen, Ilppo; Sprong, Hein; et al. (Parasites & Vectors, 2018)
BackgroundAlmost 3500 tick samples, originally collected via a nationwide citizen science campaign in 2015, were screened to reveal the prevalence and distribution of a wide spectrum of established and putative tick-borne pathogens vectored by Ixodes ricinus and I. persulcatus in Finland. The unique geographical distribution of these two tick species in Finland allowed us to compare pathogen occurrence between an I. ricinus-dominated area (southern Finland), an I. persulcatus-dominated area (northern Finland), and a sympatric area (central Finland).ResultsOf the analysed ticks, almost 30% carried at least one pathogen and 2% carried more than one pathogen. A higher overall prevalence of tick-borne pathogens was observed in I. ricinus than in I. persulcatus: 30.0% (604/2014) versus 24.0% (348/1451), respectively. In addition, I. ricinus were more frequently co-infected than I. persulcatus: 2.4% (49/2014) versus 0.8% (12/1451), respectively. Causative agents of Lyme borreliosis, i.e. bacterial genospecies in Borrelia burgdorferi (sensu lato) group, were the most prevalent pathogens (overall 17%). Candidatus Rickettsia tarasevichiae was found for the first time in I. ricinus ticks and in Finnish ticks in general. Moreover, Babesia divergens, B. venatorum and Candidatus Neoehrlichia mikurensis were reported for the first time from the Finnish mainland.ConclusionsThe present study provides valuable information on the prevalence and geographical distribution of various tick-borne pathogens in I. ricinus and I. persulcatus ticks in Finland. Moreover, this comprehensive subset of ticks revealed the presence of rare and potentially dangerous pathogens. The highest prevalence of infected ticks was in the I. ricinus-dominated area in southern Finland, while the prevalence was essentially equal in sympatric and I. persulcatus-dominated areas. However, the highest infection rates for both species were in areas of their dominance, either in south or north Finland. Peer reviewed